The mycosins, a family of secreted subtilisin-like serine proteases associated with the immunologically-important ESAT-6 gene clusters of Mycobacterium tuberculosis - Gey van Pittius, Nicolaas Claudius (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2002.